Pengaruh metode pembelajaran project based learning terhadap motivasi belajar mahasiswa prodi matematika FMIPA Universitas Mataram - Ayudia, Nurul Ulya; Pradana, Satriawan; Juliansyah, Wahyu Ari; Pratama, Muhammad Imran Ade; Auladi, Muhammad Yuzaul; Purnamasari, Nur Asmita (Semeton Mathematics Journal, 2025)
This study evaluates the impact of the Project-Based Learning (PBL) method on the learning motivation of Mathematics students at FMIPA Universitas Mataram. The primary objective is to assess the effectiveness of PBL in enhancing learning motivation and to explore the influencing factors, namely Facilities (X₁), Lecturer Role (X₂), and Skill Development (X₃). This research employs a quantitative descriptive method, with a population of 257 Mathematics students from FMIPA Universitas Mataram, covering the 2020–2023 cohorts. The sample is determined using the Stratified Random Sampling method. Data were collected through research instruments that had been tested for validity and reliability. Data analysis was conducted using descriptive analysis (pie charts, bar charts, histograms, and scatter plots) and multiple linear regression to identify the influence of the independent variables (X₁, X₂, X₃) on (Y). The findings indicate that 63.8% of the variation in learning motivation (Y) can be explained by Facilities (X₁), Lecturer Role (X₂), and Skill Development (X₃). Both simultaneous and partial tests confirm that all independent variables contribute significantly to students’ learning motivation. These results suggest that the PBL method is not only effective in enhancing learning motivation but also holds potential as an innovative teaching strategy in higher education.